(3GdcGaj aj UfGYI GdWHs - (3YOfGf GdYjf RQHj , ehab GdOjf CHh fUQ,J (B548 (3g` s ((3TgGH GdOjf Hf GdTjN UOjb GdYWGQ s)
(3ChdgG (B:s
(3JfGhd ajg GdCeQGV hCSHGHgG hCYQGVgG , hdGGdYdGL hUaJg , deG cGf GdWH jfbSe bSeg ChdjI Edi bSejf s
(3BNQgG (B:s
(3adG JYOd Yf GdSjQ MTcQ , Ke cdYGHGJ GdSaQLd hHRQ bWhfG hGddg Gdehab s
(3eQJH Ydi GdCYVGAs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B273s
GAL - (3GdLRA (B1 - (3U (B487 ; GALS - (3GdLRA (B1 - (3U (B890 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B151 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1377s
Keywords: (3GdWHs